Exploring variables related to medical surrogate decision-making accuracy during the COVID-19 pandemic. Issue 2 (February 2022) - Spalding, Rachael L.; Edelstein, Barry
Highlights: Surrogates poorly predict patient preferences on medical decision-making vignettes. Surrogates' characteristics predict the interventions they select for patients. Characteristics included intrapersonal and interpersonal variables. Surrogates with more anxiety about COVID-19 chose more intense interventions for patients. Abstract: Objective: Surrogate medical decision making is common in the United States healthcare system. Variables that may influence surrogate decision making have been proposed. Little work has examined relations between these variables and outcomes of surrogate decision making. This study investigated whether surrogates' characteristics, including their knowledge of treatment options, and interpersonal factors predicted surrogates' accuracy and intervention selections. Specifically, predictor variables included: trust in the medical profession, trait-level anxiety, depression, anxiety about COVID-19, religiosity, perceived emotional support, understanding of treatment options, empathy, willingness to accept responsibility for medical decisions, reluctance to burden others, and perceived similarity between oneself and the patient. Methods: 154 pairs of patients and their surrogates completed an online survey. Patients indicated preferred treatments in hypothetical decision scenarios. Surrogates indicated the treatment that they thought the patient would prefer. Results: When taken all together in a predictive model, the variables significantly predicted surrogatesʼ accuracy, F (6) = 3.03, R 2 = .12, p  = .008. Variables also predicted selection of intensive interventions, F (4) = 5.95, R 2 = .14, p  = .00. Surrogates reporting greater anxiety about COVID-19 selected more intensive interventions. Conclusions: Consistent with prior research, this study found that surrogates' characteristics influence the interventions they choose, with anxiety about COVID-19 having considerable bearing on their chosen interventions. Practice implications: These findings can inform development of decision-making interventions to improve surrogates' accuracy. Providers may attend to variables highlighted by this study to support surrogates, particularly within the stressful context of COVID-19 and possible future pandemics.